FATIGUE STRENGTH ANALYSIS OF CONNECTING ROD BOLT FOR LARGE POWER DIESEL ENGINE - LU YaoHui; XIANG PengLin; XIE Ning; FENG Zhen (Jixie qiangdu)
Diesel engine connecting rod bolt withstands pre-tightening force and tensile load in working process,its strength and stiffness have great effect on the performance. An assembly model of the connecting rod which had considered the detail of threaded portion was built,and the strength of those bolts were analyzed with the finite element method. On this basis,the result post-processing program was complied,and the fatigue strength of the bolts was assessed by drawing the bolt material Goodman fatigue curve. The results indicate the rigidity and static strength and the fatigue strength are all within the allowable range; the maximum stress is located in the first level thread,and the most dangerous place of fatigue damage is located in the bolt head.While the static strength and rigidity meet the requirement,using fatigue strength analysis method can find the failure position correctly. Such analysis provides reference for design of bolt.